FEMINISME CYBORG DONNA JEANNE HARAWAY: REKONSEPSI TUBUH PEREMPUAN DI DUNIA SIBER (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
This study aims to explain Donna Jeanne Haraway's cyborg feminism. The method used in this research is using a qualitative approach with the type of library. The results of this study explain and analyze Haraway's thoughts which acutely encourage alternative ways of recreating the female body in cyberspace as an unavoidable reality in today's society. Haraway's cyborg feminism highlights the category of women who have lost their authenticity as a starting point for feminist analysis, epistemology, and politics. In the context of cyborg feminism, women as part of the structure of society need to know the boundaries and meaning of their own bodies. This opportunity opens wider with cyborg situations. Efforts to reconstruct the female body in the cyber world are carried out with the following steps: (1) Fractured Identities; (2) Informatics of Domination; (3) Homework Economy; (4) Women in The Integrated Circuit; (5) The Myth of Political Identity. Keywords: Cyborg feminism, Donna Jeanne Haraway, cyberspace, body.